(untitled) (Journal of Asian Development Studies, 2025)
This article examines whether post-election reconciliation in Pakistan can become an informal constitutional practice rooted in a progressive legal culture. It poses the question of whether the country can treat reconciliation not only as a one-time but also as a regular and consistent aspect of its political existence. The analysis is conducted with the aid of normative legal techniques. It involves conceptual analysis, traditional interpretation of the constitution and statutes, a comparison with Indonesia, as well as the reconciliation process following the Charter of Democracy (2006). The principal results are tripled. Reconciliation has been infrequent and not guided by specific rules, but by elites. Second, various structural obstacles hinder reconciliation. Third, alternative dispute-resolution (ADR) and restorative justice have their potential. Based on these findings, the article suggests that a multi-layered model exists. The model involves frequent societal recognition of election results, precise provisions of victory and concessions, a standing National Reconciliation Council, published coalition accords, civic education and press responsibility programs and legal support as a code of conduct before nomination. It also requires a broader application of mediation and restorative processes in the courtroom. The model suggests that these measures should be linked to a gradual development of a legal culture, thereby providing them with normative force by referencing Islamic notions of sulh (reconciliation), maslaha (public interest), and adl (justice). This must enhance democratic stability, although it will present a challenge to implement.